ANALISIS NILAI KARAKTER DALAM PROFIL PELAJAR PANCASILA DITINJAU DARI AKTIVITAS BELAJAR IPS DI KELAS VIII SMP PLUS NURUL WAFA MUMBULSARI (2025-2026) - Moch Ali Imron; Rina Rohmawati; M. Iqbal Ibrahim Hamdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the planning process for integrating Pancasila Student Profile (P5) values by Social Studies teachers into teaching modules and learning activities in accordance with the Independent Curriculum requirements at SMP Plus Nurul Wafa Mumbulsari, Jember. The study focuses on three aspects: (1) teachers' strategies for internalizing the six P5 dimensions into module design; (2) the manifestation of P5 values in Grade VIII Social Studies learning activities; and (3) facilitating and inhibiting factors of integration. A qualitative case-study design was employed. Data were collected through participatory observation across 18 learning sessions, in-depth interviews with the Social Studies teacher and eight students, and analysis of teaching module documents. Miles-Huberman analysis was applied. Findings reveal that the teacher integrated P5 through three explicit strategies: local Jember context-based materials, differentiated learning products, and portfolio-based value assessment. The mutual cooperation and critical reasoning dimensions were most strongly manifested. The novelty of this study lies in documenting P5 integration practices within a pesantren-based school in a rural setting, a context underrepresented in existing literature.